Lockdown logistics in consultation–liaison psychiatry. (11th December 2022) - Barry, H.; Doherty, A. M.; Clancy, M.; Moore, S.; MacHale, S.
Abstract : We describe the adaptation of services to allow flexible and practical responses to the coronavirus-19 (COVID-19) public health crisis by four Consultation–Liaison Psychiatry (CLP) services; Galway University Hospital (GUH), Beaumont Hospital, University Hospital Waterford and St Vincent's University Hospital (SVUH) CLP services. This article also illustrates close collaboration with community adult mental health services and Emergency Department (ED) colleagues to implement effective community diversion pathways and develop safe, effective patient assessment pathways within the EDs. It highlights the high levels of activity within each of the CLP services, while also signposting that many of the rapidly implemented changes to our practice may herald improvements to mental health patient care delivery in the post-COVID-19 world, if our psychiatry services receive appropriate resources.